2014
DOI: 10.1002/mbo3.184
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the model sulfate reducer Desulfovibrio gigas: a comparative analysis within the Desulfovibrio genus

Abstract: Desulfovibrio gigas is a model organism of sulfate-reducing bacteria of which energy metabolism and stress response have been extensively studied. The complete genomic context of this organism was however, not yet available. The sequencing of the D. gigas genome provides insights into the integrated network of energy conserving complexes and structures present in this bacterium. Comparison with genomes of other Desulfovibrio spp. reveals the presence of two different CRISPR/Cas systems in D. gigas. Phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 107 publications
0
11
1
Order By: Relevance
“…Recent evidence suggests that Desulfovibrio magneticus , Desulfovibrio salexigens and Desulfovibrio desufuricans possess a second HcpR related sequence in their genome that was predicted to bind an 18-bp pseudopalindromic DNA sequence similar to the HcpR binding motif [23] . Interestingly, a search of the D. gigas genome [20] revealed the presence of two HcpR sequences that share 48.9% of similarity at the amino acid level, here designated by HcpR1 and HcpR2 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggests that Desulfovibrio magneticus , Desulfovibrio salexigens and Desulfovibrio desufuricans possess a second HcpR related sequence in their genome that was predicted to bind an 18-bp pseudopalindromic DNA sequence similar to the HcpR binding motif [23] . Interestingly, a search of the D. gigas genome [20] revealed the presence of two HcpR sequences that share 48.9% of similarity at the amino acid level, here designated by HcpR1 and HcpR2 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After a search in the genome of D. gigas [20] for genes that may be regulated by HcpR1, fifteen putative targets were found to contain the described consensus binding site within the respective promoter regions. Among the fifteen candidate targets, those annotated in the D. gigas genome as hypothetical proteins were disregarded, as well as those whose consensus binding site was located more than 250 bp upstream of the initiation codon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study indicated that energy metabolism of SRB is far more versatile than we considered, so that SRB can use different alternative strategies for energy conservation (5, 6). The genome sequence analysis will allow comprehensive comparisons with other SRB and pave the way for further understanding of SRB lifestyle in anaerobic deep sea environments.…”
Section: Genome Announcementmentioning
confidence: 91%
“…The MnhABCDEFG proteins are also encoded in the genomes of Dv. gigas [61] and D. toluolica Tol2 [20], though its function in SRB is unclear at present.…”
Section: Mnhabcdefg Nadh Dehydrogenasementioning
confidence: 98%